The application of chesterman's (1997 & 2000) translation strategies to the analysis of translated online news reports following nord's (1991 & 1997) functionalsit approach - Branco, Sinara de Oliveira (2007)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-graduação em Inglês e Literatura Correspondente